Socioethnic disparities in severe maternal morbidity in Western Australia: a statewide retrospective cohort study - Rhonda Marriott; Scott W White; Akilew A Adane; Brad M Farrant; Helen D Bailey; Carrington C J Shepherd (BMJ Open)
Objectives To assess the scale of ethnic inequalities in severe maternal morbidity (SMM) rates and quantify the contribution of maternal characteristics to these disparities.Design Retrospective cohort study.Setting Whole-of-population linked administrative data from 2002 to 2015 in Western Australia.Participants Women with 410 043 birth events (includes all births from the same pregnancy) of 20 weeks’ or more gestation, including terminations for congenital anomalies.Primary and secondary outcome measures Women with SMM were identified based on a composite indicator of SMM using diagnosis and procedure codes developed for use in routinely collected data. Mothers were classified into seven ethnic groups, based on their reported ethnic origin. The associations between maternal ethnic origin and SMM were examined using a log-binomial model, which estimates risk ratios (RRs) and 95% CIs. The Blinder-Oaxaca decomposition technique was employed to partition the disparity in SMM between Aboriginal and Caucasian populations into ‘explained’ and ‘unexplained’ components.Results During the study period, 9378 SMM cases were documented. In the adjusted model, Aboriginal (RR 1.73, 95% CI 1.59 to 1.87), African (RR 1.64, 95% CI 1.43 to 1.89) and ‘other’ ethnicity (RR 1.49, 95% CI 1.37 to 1.63) women were at significantly higher risk of SMM compared with Caucasian women. Teenage and older mothers and socioeconomically disadvantaged women were also at greater risk of SMM. Differences in sociodemographic characteristics explained 33.2% of the disparity in SMM between Aboriginal and Caucasian women.Conclusions There are distinct disparities in SMM by ethnicity in Western Australia, with a greater risk among Aboriginal and African women. While improvements in SES and a reduction in teenage pregnancy can potentially support a sizeable reduction in SMM rate inequalities, future research should investigate other potential pathways and targeted interventions to close the ethnicity disparity.